Action centred leadership - "Adair, John" (London, 1973)
The aim of this book is to present to the reader a wide spectrum of experience in the application of Action-Centred Leadership (ACL) train- ing to the different needs of organizations. Besides illustrating and confirming the value of this particular approach towards developing man- agement potential, it is hoped that the following chapters will also serve as a guidebook for those wishing to improve the effectiveness of the leadership in their organizations along ACL lines.
Keywords: Leadership